Optimasi Perolehan DNA Mikrobioma yang Diekstraksi dari Mekonium dan Feses Neonatus Prematur untuk diaplikasikan pada Next-Gen Sequencing 16S rRNA - Larashintya Rulita; Amarila Malik; Radhian Amandito; Rinawati Rohsiswatmo (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
The composition of the intestinal microbiome of neonates can be identified from meconium and feces by Next-Generation Sequencing (NGS) technology. However, the yield of microbiome DNA of meconium and feces has its own challenges due to the consistency and the high content of PCR inhibitors in these samples. This study aims to optimize the yield of microbiome DNA from meconium sample and feces of pre-term neonates. The DNA yield was obtained by applying certain optimized parameters, i.e., considering the replication and condition of the sample, using a particular kit for DNA extraction, and modifying the DNA elution of the column purification. The genomic DNA obtained was quantified and confirmed using Polymerase Chain Reaction. Results showed that the best DNA yield was achieved by replicating the number of samples twice in the pre-extraction stage, working on fresh meconium and feces samples instead, and suspended the sample in ddH2O prior to extraction process as observed on agarose gel visualization with UV trans-illuminator, as well as in quantitative measurement by a nano spectrophotometer. The best extraction process was using MP Biomedical FastDNA Spin Kit for Soil, in addition to the use of an elution buffer in a smaller volume, resulting in a higher concentration and purity of DNA. In conclusion, we were able to obtain an optimized yet reliable DNA yields, especially from meconium, which fulfilled the quality and quantity requirement for further sequencing process of microbiome.